Adaptation and morphometric characterization of Boer Goat in Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
The present study was conducted to evaluate the adaptability and characterize Boer goat morphometrically under the farming condition of Bangladesh. Data on adaptability and characterization were collected from the imported flock of Boer goat maintained at American Dairy Limited, Sreepur, Gazipur. A total of 31 Boer goats (15 males and 16 females) at birth (0), 3, 6, 9, and 12 months of age were considered for morphometric characterization. From the study, it was revealed that Boer goats were adapted easily in our climatic and farming conditions. All the body measurements (body length, heart girth, height at wither, head length, head width, ear length, ear width, tail length) in both sexes were significantly (p